Simultaneous Bilateral Facial Nerve Paralysis in a 4-Year-Old Child: A Rare Occurrence - Mehta, Madhuri; Gupta, Vani Krishana; Pandurangi, Aniketh; Mehta, Navroz (Annals of Otology and Neurotology, 2019)
Paralysis of the facial nerve (cranial nerve VII) is a relatively uncommon entity in children. It not only results in weakness of the facial musculature affecting the facial expressions, eye closure, and oral competence, but also causes psychological and emotional trauma to the child and parents. Unilateral palsy is usually idiopathic, whereas bilateral palsy usually has an underlying cause. We report a case of a 4-year-old girl who presented to us with simultaneous facial nerve paralysis where the second side was involved within 7 days of the first, before its complete resolution. Evaluation of the patient and the possible etiologies of bilateral facial palsy have been discussed further.
Keywords: Bell’s palsy; facial nerve; simultaneous paralysis